2021
DOI: 10.1007/s11033-021-06304-1
|View full text |Cite
|
Sign up to set email alerts
|

Two novel microRNAs and their association with absolute blood pressure parameters in an urban South African community

Abstract: MicroRNAs are important in development of disease, and description of novel microRNAs adds to the pool of microRNAs that can be targeted for diagnostic and therapeutic purposes in disease. Herein, we aimed to describe novel microRNAs in a normotensive and hypertensive African population and relate their expression to blood pressure parameters and hypertension status. Previous work using next-generation sequencing showed differential expression of two novel microRNAs in the blood of normotensives and hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Using a microarray, Li et al [ 106 ] demonstrated that out of the total miRNAs detected in the experiment, 46 miRNAs were found to be profoundly expressed in hypertensive patients suggesting the miRNA contribution on the pathogenesis of hypertension [ 106 ]. Furthermore, dysregulation of miR-126-3p, 182-5p, and 30a-5p expression is evident to be the culprit of hypertension progression in the South African population meanwhile dysregulation of two novel miRNAs, miR-novel-chr1_36178 and miR-novel-chr15_18383, was significantly correlated with the SBP and DBP of the same population [ 104 , 107 ]. In addition, an elevation of the circulated miR-505 plasma level is found among spontaneously hypertensive rats and angiotensin II-infused mice related to endothelial dysfunction and inflammation [ 105 ].…”
Section: Epigenetic Of Hypertensionmentioning
confidence: 99%
“…Using a microarray, Li et al [ 106 ] demonstrated that out of the total miRNAs detected in the experiment, 46 miRNAs were found to be profoundly expressed in hypertensive patients suggesting the miRNA contribution on the pathogenesis of hypertension [ 106 ]. Furthermore, dysregulation of miR-126-3p, 182-5p, and 30a-5p expression is evident to be the culprit of hypertension progression in the South African population meanwhile dysregulation of two novel miRNAs, miR-novel-chr1_36178 and miR-novel-chr15_18383, was significantly correlated with the SBP and DBP of the same population [ 104 , 107 ]. In addition, an elevation of the circulated miR-505 plasma level is found among spontaneously hypertensive rats and angiotensin II-infused mice related to endothelial dysfunction and inflammation [ 105 ].…”
Section: Epigenetic Of Hypertensionmentioning
confidence: 99%